DEVELOPMENT AND CLINICAL EVALUATION OF TOPICAL HYDROQUINONE NIOSOMAL GEL FORMULATION FOR THE TREATMENT OF MELASMA - AMMAR, AMAL A.; SALEM, HODA A.; ELADAWY, SHEREEN A.; ELSAMAD, ZINAB I. ABD; KOHAF, NEVEEN A. (International Journal of Applied Pharmaceutics, 2020)
Objective: The goal of the present study was to develop niosomal gel as a nanocarrier for improved depigmentation effect of hydroquinone (HQ). As well as to evaluate the prepared niosomes for entrapment efficiency, transmission electron microscopy (TEM), zeta potential, and in vitro release study. As an ultimate point of the objectives was to evaluate the best-prepared niosomal gel formula clinically in well-diagnosed patients of melasma and the results were compared with a commercial product. Methods: The effect of incorporation of co-surfactant such as Tween 20, Tween 40, and Tween 60 with Span 80, was studied to determine the highest entrapment efficiency and the desired release rate. Niosomes showed the highest entrapment efficiency was incorporated in different gelling agents like Carbopol 934 and Carboxymethylcellulose sodium (CMC Na) with different concentrations. Accelerated stability testing of HQ from niosomal gel formulations; the expiry date t90 was estimated. The best-prepared niosomal gel formula was studied clinically in patients of melasma and the results were compared with the commercial product (Clearique 2%)®Delta Pharma Company. Results: There was a significant increase in the clinical efficacy of the niosomal therapy and a highly significant decrease regarding to modified melasma area and severity index (MASI), duration to achieve improvement, side effects, and the recurrence of melasma in patients treated with niosomal gel compared to the commercial product. Conclusion: The incorporation of hydroquinone in niosomal gel improves its therapeutic effect regarding clinical effect, duration of treatment, side effects, recurrence and patient compliance.